Socialisation scenes in the health behaviour of teacher students at different levels of teacher training - Moravecz, Marianna; Kovács, Karolina Eszter; Kozma, Bettina (Frontiers in Sports and Active Living, 2025)
The issue surrounding sport and health as valuable categories spans across generations. It is now widely recognised that inherited, lifestyle, and environmental factors influence an individual's health. Our study investigated the impact of family as the primary area of socialisation and school as the secondary area. Data collection commenced online in the spring of 2020, focusing on pedagogical students from the University of Nyíregyháza (N = 194). Among our research sample, kindergarten teachers exhibited the lowest indicators regarding risk behaviour. Conversely, students specialising in teaching demonstrated the most favourable outcomes regarding physical activity, with a rate of 20.6%. The family's influence presents a significant effect in both positive and negative aspects. When families prioritise instilling a love for sports, students tend to have a more favourable view of their health and aspire to embody exemplary values in the future; however, the family also presents a less encouraging image. Analysing the impact of residence reveals that a greater percentage of individuals from immigrant backgrounds identified the family as their role model (27.2%) compared to their counterparts residing in the county seat, while the influence of the teacher's personality was minimal. These findings align with earlier research. The students participating in our study hailed from the underprivileged Northern Great Plain region, which contributes to an increased search for security. The research indicates that family emerged as a significant example of values, and the objective is to foster positive health behaviours in both areas equally.